Relationship of left ventricular outflow tract velocity time integral to treatment strategy in submassive and massive pulmonary embolism - Antoine, David; Chuich, Taylor; Mylvaganam, Ruben; Malaisrie, Chris; Freed, Benjamin; Cuttica, Michael; Schimmel, Daniel (Pulmonary circulation, 2020)
Pulmonary embolism is associated with high rates of mortality and morbidity. It is important to understand direct comparisons of current interventions to differentiate favorable outcomes and complications. The objective of this study was to compare ultrasound-accelerated thrombolysis versus systemic thrombolysis versus anticoagulation alone and their effect on left ventricular outflow tract velocity time integral. This was a retrospective cohort study of subjects ≥18 years of age with a diagnosis of submassive or massive pulmonary embolism. The primary outcome was the percent change in left ventricular outflow tract velocity time integral between pre- and post-treatment echocardiograms. Ultrasound-accelerated thrombolysis compared to anticoagulation had a greater improvement in left ventricular outflow tract velocity time integral, measured by percent change. No significant change was noted between the ultrasound-accelerated thrombolysis and systemic thrombolysis nor systemic thrombolysis and anticoagulation groups. Pulmonary artery systolic pressure only showed a significant reduction in the ultrasound-accelerated thrombolysis versus anticoagulation group. The percent change of right ventricular to left ventricular ratios was improved when systemic thrombolysis was compared to both ultrasound-accelerated thrombolysis and anticoagulation. In this retrospective study of submassive or massive pulmonary embolisms, left ventricular outflow tract velocity time integral demonstrated greater improvement in patients treated with ultrasound-accelerated thrombolysis as compared to anticoagulation alone, a finding not seen with systemic thrombolysis. While this improvement in left ventricular outflow tract velocity time integral parallels the trend seen in mortality outcomes across the three groups, it only correlates with changes seen in pulmonary artery systolic pressure, not in other markers of echocardiographic right ventricular dysfunction (tricuspid annular plane systolic excursion and right ventricular to left ventricular ratios). Changes in left ventricular outflow tract velocity time integral, rather than echocardiographic markers of right ventricular dysfunction, may be considered a more useful prognostic marker of both dysfunction and improvement after reperfusion therapy.